Pengaruh Suasana Toko, Promosi dan Keberagaman Produk terhadap Keputusan Pembelian pada Listy Mart - Moh Aziz Fikri; Taufik Akbar; Kukuh Harianto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to determine the influence of store atmosphere, promotions and product diversity on purchasing decisions at Listy Mart. This type of research is quantitative research. This research data was obtained through primary and secondary data. The population in this research are consumers at Listy Mart. The sample in this research was 213 consumers with a sampling technique using the Slovin formula. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that the partial t test results show that the shop atmosphere, promotion and product diversity variables influence purchasing decisions at Listy Mart. Simultaneous F test results: store atmosphere, promotions and product diversity influence purchasing decisions at Listy Mart